DEGROWTH, STEADY STATE AND CIRCULAR ECONOMIES: ALTERNATIVE DISCOURSES TO ECONOMIC GROWTH - CHARONIS, GEORGE-KONSTANTINOS (Society Register, 2021)
Criticisms of the neoclassical economic framework and perpetual growth in GDP terms are not a new phenomenon, although recent years have seen increasing interest in alternative and ecological discourses including degrowth, steady-state and circular economics. Although these may initially appear as distinctly different discourses, they are highly compatible and comparable, sharing similar, often nearly identical principles and policy proposals. A more collaborative, joined-up approach aimed at integrating alternative discourses is required in order to build a coherent, credible, well-supported alternative, as there is more uniting than dividing these critical voices, particularly in the face of mainstream political and economic debates that are shaped by neoclassical economics.